2020
DOI: 10.1177/0033354920966004
|View full text |Cite|
|
Sign up to set email alerts
|

National Support for a Menthol Cigarette Sales Ban

Abstract: Objectives The US Food and Drug Administration (FDA) and local jurisdictions have different authorities to regulate menthol cigarettes, and a growing number of localities and the FDA are considering these policy options. The objective of this study was to update previous research on public support for a menthol ban, including examining differences in support by demographic factors, geographic region, and smoking status. Methods We assessed policy support among a cross-sectional sample of 2871 adults aged 18-64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
3
2
Order By: Relevance
“…28 Similar to comparable studies, we found smokers were less likely to support a flavour ban. 26 Unlike existing work, 28 we found participants from high-income households were less likely to support a flavoured e-cigarette sales ban.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…28 Similar to comparable studies, we found smokers were less likely to support a flavour ban. 26 Unlike existing work, 28 we found participants from high-income households were less likely to support a flavoured e-cigarette sales ban.…”
Section: Discussioncontrasting
confidence: 84%
“…This study assessing public support for tobacco and e-cigarette policies among adults in rural California found a majority support a comprehensive flavoured tobacco or e-cigarette product sales ban (including menthol) with higher levels of support for other policies to regulate e-cigarette products. Support for a flavoured tobacco ban (58%) in our study was higher than a 56% rate from a nationally representative online panel 26. Support for a flavoured e-cigarette sales ban (59%) was lower compared with a 63% rate from an online panel,27 but similar to a 57% rate reported from a 2015 representative sample of California voters 28…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…There is national support for a menthol cigarette sales ban. [45] The health cost of smoking-related illness in the US is approximately $300 billion, and smoking results in 480,000 deaths per year. [46] In NYC, the prevalence of menthol smoking among people who currently smoke is about 50% with the highest prevalence observed among non-Latino Black individuals (84%) and the lowest prevalence among non-Latino White individuals (26%).…”
Section: Discussionmentioning
confidence: 99%